Alinhamento estratégico em Tecnologia da Informação: um estudo em cooperativas agropecuárias - Silva, Sidney Verginio da (2018)
This paper presents the results of a study on strategic alignment in Information Technology (IT), carried out in two agricultural cooperatives. The objective of the study was to identify if there is strategic alignment of IT in the organizations analyzed, also identifying the degree of alignment. This research is justified given the relevance of agribusiness to the Brazilian economy, and, in addition, the importance that agricultural coopera tives have for rural producers. Because of their specificities, which differ from other types of organizations, cooperatives have demanded a more professional management, capable of carrying out a plan that can lead the organization to achieve better resul ts, adding value to its activities and its members. In addition, Information Technology has been able to assist organizations not only in their routine activities, but also in the definition of organizational structures and in support of planning and decision-making. However, for this it is necessary that IT is acquired and used in a way that is aligned with the business and objectives of the organization. The results of study show that the Information Technology is still very directed only to support the r outine operations of the cooperatives studied, without being used as a competitive differential. The development of strategic IT planning and the quest for IT governance are challenges to be overcome by the management of these organizations. These results bring new discussions to the studies on strategic alignment and IT use in agribusiness, filling some existing gaps, mainly in relation to the application and validation of strategic alignment models and the promotion of alignment in agricultural cooperatives. Finally, these discoveries can be used by managers of cooperative organizations and support agencies to improve the use of IT in agribusiness management, in order to add value and improve the results of all those involved in the agribusiness production chain.